Peran Badan Usaha Milik Desa (BUMDes) dalam Upaya Meningkatkan Pendapatan Petani di Desa Sidan, Kecamatan Gianyar, Kabupaten Gianyar - AWANGGA, I PUTU YOGA; ANTARA, MADE; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.2, Desember 2024, 2024)
The Role of Village-Owned Enterprises (BUMDes) in Efforts to Increase Farmers' Income in Sidan Village, Gianyar District, Gianyar Regency.  Village Owned Enterprises (BUMDes) are organizations formed by the village government, and the community runs these organizations according to the needs and economy of the village. This study aims to determine the role of Village-Owned Enterprises (BUMDes) in an effort to increase farmers' income, and how to increase farmers' income in Sidan Village before and after the existence of Village-Owned Enterprises (BUMDes). This research was conducted in Sidan Village, Gianyar Regency. By researching BUMDes named BUMDes Mertha Rahayu. This research is a type of qualitative and quantitative research. The informants in this study were BUMDes administrators and farmers. Data collection methods used are in-depth interviews, structured interviews and documentation. The data analysis used is descriptive qualitative using a Likert scale and income analysis. The results of the study show that BUMDes have played a role in efforts to increase farmers' income. This role is manifested in the form of providing capital loans to farmers with low interest, helping farmers to access credit easily, then helping farmers make it easier to get production facilities at lower prices, and can be paid after harvest.